2021
DOI: 10.2174/1871527320666210526160926
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies for Parkinson’s Disease: Progression of Clinical Development

Abstract: : Parkinson’s disease is a common neurodegenerative disease affecting the movement and wellbeing of most elderlies. The manifestations of Parkinson’s disease often include resting tremor, stiffness, bradykinesia and muscular rigidity. The typical hallmark of Parkinson’s disease is the destruction of neurons in the substantia nigra and the presence of Lewy bodies in different compartments of the central nervous system. Due to various limitations to the currently available treatments, immunotherapies have emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Another promising approach is to promote the clearance of and prevent the cellular spread of α-synuclein through immunotherapy [ 120 ]. There are several agents currently under study, including Cinpanemab and Prasinezumab, which are both used in passive immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Another promising approach is to promote the clearance of and prevent the cellular spread of α-synuclein through immunotherapy [ 120 ]. There are several agents currently under study, including Cinpanemab and Prasinezumab, which are both used in passive immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Following selection, a nanobody, PFFNB2, was identified that could not inhibit the aggregation of αSyn monomer, though it can specifically recognize and significantly dissociate αSyn fibrils. A series of humanized monoclonal antibodies BIIB054 (cinpanemab), MEDI1341, AFFITOPE, and PRX002 (prasinezumab) were under clinical development [ 422 ]. However, despite the huge financial costs, the results of these developments were rather discouraging.…”
Section: Treatment and Optimization Of The Condition Of Patients With Pdmentioning
confidence: 99%
“…They reported the pharmacokinetics, safety and tolerability in phase I, prasinezumab did not show relevant clinical benefits according to MDS-UPDRS outcomes. [98][99][100][101] Inhibition of RGMa: The Future Concept?…”
Section: Current Ongoing Disease Modifying Interventions In Pdmentioning
confidence: 99%